The Relationship Between Mother's Knowledge Level and Parenting Patterns with Stunting in Toddlers Aged 12–59 Months - Dike Fitriani; Abdullah; Alifiyanti Muharramah; Desti Ambar Wati (CV. CENDIKIA JENIUS INDONESIA, 2026)
Introduction: Stunting remains a major global and national public health problem, including in Sukamulya Village, where a high prevalence of growth disorders among toddlers indicates the need for further investigation of contributing factors. Objective: This study aimed to analyze the relationship between mothers’ knowledge and parenting patterns and the incidence of stunting in toddlers aged 12–59 months. Methods:This quantitative study applied a descriptive–correlative approach with a cross-sectional design. A total of 63 mothers were selected using a purposive sampling technique. Data were collected using questionnaires on maternal knowledge and parenting patterns, and analyzed using the Gamma test. Results: The findings show that most mothers had good knowledge (81.0%) and good parenting practices (57.1%), while the proportion of toddlers categorized as stunted (short and very short) reached 19.1%. There was a significant relationship between maternal knowledge and stunting (p = 0.000), as well as between parenting patterns and stunting (p = 0.000). Conclusion : In conclusion, higher maternal knowledge and optimal parenting practices are associated with a lower risk of stunting. Strengthening health education on balanced nutrition, sanitation, and increasing mothers’ participation in community health services is recommended to support effective stunting prevention.